Overexpression of luxS Promotes Stress Resistance and Biofilm Formation of Lactobacillus paraplantarum L-ZS9 by Regulating the Expression of Multiple Genes - Liu, Lei; Wu, Ruiyun; Zhang, Jinlan; Li, Pinglan (Frontiers in Microbiology, 2018)
Probiotics have evoked great interest in the past years for their beneficial effects. The aim of this study was to investigate whether luxS overexpression promotes the stress resistance of Lactobacillus paraplantarum L-ZS9. Here we show that overexpression of luxS gene increased the production of autoinducer-2 (AI-2, quorum sensing signal molecule) by Lactobacillus paraplantarum L-ZS9. At the same time, overexpression of luxS promoted heat-, bile salt-resistance and biofilm formation of the strain. RNAseq results indicated that multiple genes encoding transporters, membrane proteins and transcriptional regulator were regulated by luxS. These results reveal a new role for LuxS in promoting stress resistance and biofilm formation of probiotic starter.